Charting churches in a changing Europe: Charta Oecumenica and the process of ecumenical encounter - Noble, Tim; Noble, Ivana; Brinkman, M. E.; Hilberath, Bernd Jochen (Currents of encounter studies on the contact between Christianity and other religions, beliefs, and cultures, 2006)
En route to koinonia: church communion in transition /Martien E. Brinkman --The significance of the Charta Oecumenica today: critical comments from a Protestant perspective /Kajsa Ahlstrand --An assessment of the Charta Oecumenica from a Roman Catholic perspective /Peter de Mey --Church communion and the reception of ecumenical dialogues: an Orthodox perspective /Dorin Oancea --Enough is enough?: preconditions for church communion from a Lutheran perspective /Oliver Schuegraf --The modern inculturation debate and the catholicity of the church /Martien E. Brinkman --The catholicity of the church: a matrix of faith and life in view of God's final kingdom /Anton Houtepen --Uniting Europe as a challenge to the future of national churches /Eddy Van der Borght --Gradual church communion as an ecumenical model?: some remarks from a Roman Catholic perspective /Johannes Oeldemann --The Roman Catholic understanding of sacramentality and its potential for church unity /Maria Clara Lucchetti Bingemer --From the sacramentality of the church to the sacramentality of the world /Ivana Noble --Epilogue /Bernd Jochen Hilberath --Appendix:Text of the Charta Oecumenica.